A review on the anomalous exothermic behavior of bubbles in aluminum induced by electron irradiation - Qicong Chen; Yupeng Yin; Wentuo Han; Xiaoou Yi; Pingping Liu; Qian Zhan; Somei Ohnuki; Farong Wan (Journal of Materials Research and Technology)
Anomalous exothermic phenomenon (AEP) under bubble irradiation in solids has captured widespread interest in the energy field. AEP was discovered during the transmission electron microscope (TEM) observation of deuterium-implanted aluminum. Under the irradiation of TEM electron beam, deuterium (D) bubbles led to AEP, causing the surrounding single-crystal aluminum to instantaneously transform into polycrystalline. The released heat was estimated as about 160 MeV. AEP has been discovered in different gas bubbles such as hydrogen, helium, argon, and neon. The influencing factors of AEP can be summarized as the bubble morphology and pressure, gas type and density, electron beam energy, and irradiation time. The factor interrelationships and the AEP threshold are discussed. In conjunction with experimental phenomena and simulation, the mechanism of AEP is speculated to be the plasma formation within the gas bubble. The generation of this substantial energy only requires the irradiation of bubbles with a beam of energetic particle. Such convenient, efficient, and controllable energy source is attractive. AEP may provide a potent new energy form.